Reframing conversations on institutional autonomy, academic freedom, and accountability in the context of emerging managerialism and corporatism in South African higher education - Ntshoe, I.; Faller, F. (South African Journal of Higher Education, 2025)
Institutional autonomy and academic freedom have for centuries been the bedrock of a typical university. Universities have always prided themselves as being accountable to their convocations on curriculum, who teaches it, who is taught, how it is taught, and the priorities of a research agenda. However, there have always been challenges to this autonomy and freedom, from states and estates, religious powers, and ideological factions throughout university history. The challenges have recently come from rising new managerialism, corporatism, and performativity in university activities, making institutional accountability increasingly answerable to external interests. This article examines changing discourses in higher education in the contexts of transformational imperatives and emerging managerialism, corporatism, and performativity. This intersection of transformational imperatives and market incursions dictates reinterpretation of institutional autonomy, academic freedom and new approaches to accountability in higher education globally and in South Africa. Neither academic freedom nor institutional autonomy can flourish without responsiveness to notions of accountability